2019
DOI: 10.1128/iai.00646-18
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Gardnerella vaginalis and Vaginolysin with the Apical versus Basolateral Face of a Three-Dimensional Model of Vaginal Epithelium

Abstract: Studies have implicated Gardnerella vaginalis as an important etiological agent in bacterial vaginosis (BV). It produces a cholesterol-dependent cytolysin, vaginolysin (VLY). In this study, we sought to characterize the interaction between vaginal epithelium, G. vaginalis, and VLY using EpiVaginal tissues from MatTek. These tissues are three-dimensional and have distinct apical and basolateral sides, enabling comparison of the effects of G. vaginalis and VLY following exposure to either side. We measured cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 89 publications
(99 reference statements)
0
30
2
Order By: Relevance
“…VLY is toxic to a variety of cell types, including erythrocytes, epithelial cells, and neutrophils [3,4,12]. Interestingly, however, we recently reported that the apical face of a three-dimensional tissue model of human vaginal epithelium is relatively resistant to VLY, and our data also showed that there was reduced expression of CD59 on the apical side [13]. This finding seems to contradict in vivo evidence suggesting that Gardnerella spp.…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…VLY is toxic to a variety of cell types, including erythrocytes, epithelial cells, and neutrophils [3,4,12]. Interestingly, however, we recently reported that the apical face of a three-dimensional tissue model of human vaginal epithelium is relatively resistant to VLY, and our data also showed that there was reduced expression of CD59 on the apical side [13]. This finding seems to contradict in vivo evidence suggesting that Gardnerella spp.…”
Section: Introductioncontrasting
confidence: 75%
“…We recently reported that in a stratified, polarized model of the human vaginal epithelium, VLY Type 2 cytotoxicity was limited to the basolateral side. Apical (lumenal) cells were resistant to the toxin [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VLY induces pro-inflammatory signaling, by IL-8 production in human epithelial cells. 44 , 46 , 47 Bacterial VLY, like most of CDCs, uses cholesterol from the cholesterol-rich membrane for integration and recognizes specifically 3-β-hydroxy group by threonine/leucine pair of cholesterol recognition motif, located in the 1 st loop. 48 Results of Gelber et al 44 showed that VLY binds indirectly to cholesterol, involving hCD59 protein as the receptor.…”
Section: Potential Role Of Microbiome In Endometrial Cancer Initiatiomentioning
confidence: 99%
“…Most clinical isolates of G. vaginalis from bacterial vaginosis patients express VLY [20]. VLY promotes IL-1β release from epithelial cells, and more IL-1β is stimulated from bacteria that reach the basolateral surface [293]. The increased cytokine production is due to the increased amount of CD59 expressed on the basolateral surface [293].…”
Section: Intermedilysin (Ily) and Vaginolysin (Vly)mentioning
confidence: 99%
“…VLY promotes IL-1β release from epithelial cells, and more IL-1β is stimulated from bacteria that reach the basolateral surface [293]. The increased cytokine production is due to the increased amount of CD59 expressed on the basolateral surface [293]. Interestingly, VLY also stimulates microvesicle shedding from the apical surface [294].…”
Section: Intermedilysin (Ily) and Vaginolysin (Vly)mentioning
confidence: 99%